Treatment of Lentigines: A Systematic Review. Issue 1 (January 2023) - Mukovozov, Ilya; Roesler, Jordanna; Kashetsky, Nadia; Gregory, Allison
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Treatments for solar lentigines include topical and physical therapies, including chemical peels, lasers, intense pulsed light, and cryotherapy. A direct comparison of treatment methods and their efficacy is lacking. OBJECTIVE: To compare treatment efficacy and adverse events for different treatment modalities for lentigines. METHODS: Cochrane, MEDLINE, and Embase databases were searched on August 25, 2021. Studies were included if they met our predetermined population, intervention, comparator, outcomes, study design framework. Results are presented in narrative form. RESULTS: Forty-eight articles met the inclusion criteria, representing a total of 1, 763 patients. Overall, combination-based treatments showed the greatest frequency of cases with complete response (65%, n = 299/458), followed by laser-based treatments (43%, n = 395/910), topical retinoids (21%, n = 12/57), cryotherapy (15%, n = 25/169), and peels (6%, n = 8/125). Adverse events occurred most commonly while using topical retinoids (82%, n = 23/28), followed by combination-based treatments (39%, n = 184/466), cryotherapy (33%, n = 47/144), laser-based treatments (23%, n = 173/738), and peels (19%, n = 21/110). CONCLUSION: Despite heterogeneity of included study designs, patient populations, treatment regimens, and outcome measures, our results suggest that combination-based treatments and laser-based treatments were the most efficacious treatment modalities. Although cryotherapy was previously considered first-line, our results show that it has substantially lower pooled response rates compared with other treatment modalities.